A influência dos campos pessoal e organizacional na decisão do preço sob a perspectiva de tolerância ao risco - Borges, Lisiany Andrino (2021)
This research aimed to identify the influence of the personal and organizational field in the price decision from the perspective of risk tolerance. Thus, it is based on the Prospect Theory proposed by Kahneman and Tversky in 1979. To this end, the effect of the demographic characteristics of managers and consumers on pricing and price decisions, considering risk tolerance was verified; additionally, it was verified if there are significant differences in the decisions about the price in the personal and in the organizational field; and also influence of the availability heuristic and its biases in decision making in relation to price. In order to meet these objectives, an experiment was carried out under laboratory conditions, applied virtually to 174 students with a specialization in the areas of administration and accounting offered by the Federal University of Uberlândia. The participants were randomly directed to two groups (personal and organizational field), so half of the students answered the questionnaire that brought questions about decisions to buy or not a product based on price (personal field), and the rest assumed the role of company manager (organizational field) deciding on the price. The data were analyzed statistically by logistic regression, and the results indicate that the field in which the decision was made doesn’t affect the individual's risk tolerance, a result that differs from other studies in the area. In addition, it was possible to conclude that the following variables influence the manager in deciding the price: age, marital status, currently works with management, period that he has worked as a manager, brand_price, brand_warranty.And the variables that influence the consumer are: sex, education level and currently works with management. Additionally, it was found that the greater the risk tolerance of the participant, the greater the effect of the availability heuristic in decisions about the price, having influence of the biases ease of recall and the assumed associations. The findings are consistent with the Prospect Theory, which argues that individuals take risks to avoid a loss, and avoid risks in situations that can obtain a gain. Such findings contribute to indicate the direction of the manager’s behavior and consumer’s behavior when selling or purchasing a product, based on its price, in view of the risk tolerance.